Comparing the Musculoskeletal Disorders of the Neck Between the Teachers of Physical Education and Other Majors in High Schools of Tehran City, Iran - Elham Rahimipour Najafabadi; Reza Rajabi; Mohammad Hossein Alizade; Ali Mirabedi (Sport Sciences and Health Research)
Introduction: Musculoskeletal Disorders (MDs) largely contribute to occupational diseases in the workplace. Prevention from these disorders requires their evaluation in different occupations. This study aimed to compare the MDs of the neck between the teachers of Physical Education (PE) and those of the other majors in the high schools of Tehran City, Iran.Methods: The study sample included 180 teachers of mathematics, PE, and the religion and lifestyle in the high schools of Tehran (with the Mean±SD age of 42.11±6.65 years, and the Mean±SD weight of 72.28±12.98 kg). The participants were selected from 19 districts of the Tehran Departments of Education using multistage cluster sampling. The standard Nordic questionnaire was administered to investigate MDs among the teachers. The obtained data were analyzed with the Chi-square test to compare the MDs of the neck between the three groups of teachers.Results: A significant relationship was observed between the neck problems of the female (P=0.016) and male (P=0.017) PE teachers and the other teachers. Moreover, the neck problems were associated with the teaching experience (P=0.024) and teaching major (P=0.004).Conclusion: Based on the results, it seems that regular exercise can reduce the developing risk of MDs in the neck. Thus, this study recommends the performance of regular exercise and the correction of job-related postures to all teachers.